Nuclear Energy Levels Scheme of Sc46 by Using FPD6 and KB3G Interaction - Hasan Ali Kadhim; Majeed , Firas Zuhair (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Nuclear energy levels in with modest occupancy of the fp-LS shell have been studied within shell model calculations. The interactions used to determine the nuclear energy levels are FPD6, KB3G, and FPY using the fp shell and d3f7cospn for 1d3/21f7/2 model space. Results are compared with each other, and with the existing experimental data, there is clear agreement with some results. Aside from the excellent agreements in the replicated values of energy levels scheme, using model space interactions is the best-fitted two-body matrix element in the fp shell model space. Particularly below 3MeV, the overall estimation of the replicated data is excellent. The wave vectors and analysis are represented in the so-called diagrammatic notation, and all inscriptions are provided in this style. A single particle vector is generated by utilizing the oscillator’s potential and considering as the core for the fp shell model space and as the inactive core for the d3f7 model space. Results are obtained for all examined nuclei using the OXFORD BEUNES AIRES SHELL MODEL CODE.